2011
DOI: 10.1167/iovs.10-6581
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Locus for Autosomal Dominant Primary Open Angle Glaucoma on 4q35.1-q35.2

Abstract: This study identifies a new primary open angle glaucoma locus, GLC1Q, in a region on chromosome 4 not previously associated with glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…8 Further, 21 POAG susceptibility loci have been identified by linkage studies, including 14 assigned as GLC1A-GLC1N and 10 that remain unassigned. 1,[9][10][11][12] However, only three underlying genes have been identified at these loci, MYOC in GLC1A, 13 OPTN in GLC1E, 14 and WDR36 in GLC1G; 15 these genes account for o5% of glaucoma cases.…”
Section: Introductionmentioning
confidence: 99%
“…8 Further, 21 POAG susceptibility loci have been identified by linkage studies, including 14 assigned as GLC1A-GLC1N and 10 that remain unassigned. 1,[9][10][11][12] However, only three underlying genes have been identified at these loci, MYOC in GLC1A, 13 OPTN in GLC1E, 14 and WDR36 in GLC1G; 15 these genes account for o5% of glaucoma cases.…”
Section: Introductionmentioning
confidence: 99%
“…15 To date, over 50 mutations have been identified in BCD patients, with at least one mutation in each of the gene's 11 exons. [9][10][11][12][13][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Genotype analysis has shown that the most common pathologic CYP4V2 mutation is c.802-8_810del17insGC, which results in deletion of exon 7 in the mature transcript, though other mutations in each exon are also Copyright 2014 The Association for Research in Vision and Ophthalmology, Inc. www.iovs.org j ISSN: 1552-5783 linked to the disease. 16,17,28 Additionally, a relatively common polymorphism in CYP4V2 (rs13146272; Q259K), with a minor allele frequency of 45%, has been associated with deep vein thrombosis.…”
mentioning
confidence: 99%
“…POAG’s complex and variable phenotype intimate’s multifactorial etiology, for instance, multifaceted genetic network (one or more genes) along with environmental influences. There are several genetic loci reported to be directly involved in disease onset or considered risk elements found by Genome-wide association studies ( Porter et al, 2011 , Kader et al, 2017 ). MYOC (myocilin) is the very first gene identified to cause POAG in an autosomal dominant fashion.…”
Section: Introductionmentioning
confidence: 99%